BRAF mutant appendiceal adenocarcinoma differs from colorectal cancer but responds to BRAF-targeted therapy - Vinay K. Pattalachinti; Emaan Haque; Mahmoud Yousef; Abdelrahman Yousef; Saikat Chowdhury; Michael Overman; Christine M. Parseghian; Van K. Morris; Bryan Kee; Ryan W. Huey; Kanwal Raghav; Colin M. Court; et al. (npj Precision Oncology)
Abstract Appendiceal Adenocarcinoma (AA) is a rare gastrointestinal cancer with no FDA-approved targeted therapies. Here, we retrospectively compare BRAF-mutant AA and colorectal cancer (CRC). BRAF mutation is rare in AA (3%). Unlike CRC, BRAF V600E AA is not associated with poor prognosis, female sex, microsatellite instability, mucinous histology, or poor differentiation. In both cancers, BRAF V600E but not atypical BRAF mutations are mutually exclusive with other Ras-activating mutations. BRAFV600E + EGFR inhibition shows efficacy in BRAF V600E AA (disease control rate = 80%, median progression-free survival = 7.1 months).